UNIFORM REQUIREMENTS FOR MANUSCRIPT SUBMITTED TO BIOMEDICAL JOURNALS: WRITING AND EDITING FOR BIOMEDICAL PUBLICATION (2008) - T. A. Kazakovceva (Столичная издательская компания, 2016)
Uniform Requirements for Manuscript Submitted to Biomedical Journals: Writing and Editing for Biomedical Publication (2008).